2003
DOI: 10.1016/s0896-6273(03)00165-x
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal CA3 NMDA Receptors Are Crucial for Memory Acquisition of One-Time Experience

Abstract: Lesion and pharmacological intervention studies have suggested that in both human patients and animals the hippocampus plays a crucial role in the rapid acquisition and storage of information from a novel one-time experience. However, how the hippocampus plays this role is poorly known. Here, we show that mice with NMDA receptor (NR) deletion restricted to CA3 pyramidal cells in adulthood are impaired in rapidly acquiring the memory of novel hidden platform locations in a delayed matching-to-place version of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
350
4
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(408 citation statements)
references
References 39 publications
49
350
4
2
Order By: Relevance
“…accordance with evidence that demonstrate the importance of this structure in the rapid acquisition of new information (Nakazawa et al 2003;Leutgeb et al 2006;Miyashita et al 2009). In our task, the odor combination in a paired associate is session unique (see Materials and Methods).…”
Section: Discussionsupporting
confidence: 87%
“…accordance with evidence that demonstrate the importance of this structure in the rapid acquisition of new information (Nakazawa et al 2003;Leutgeb et al 2006;Miyashita et al 2009). In our task, the odor combination in a paired associate is session unique (see Materials and Methods).…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were obtained with CA3-specific neurotoxic lesions (Lee and Kesner 2003). Nakazawa et al (2003) reported similar findings with a mouse strain in which the function of CA3 NMDA receptors was disrupted. These mutant mice were impaired in learning a novel platform location in a modified water maze task, whereas they were normal in finding familiar platform locations.…”
supporting
confidence: 82%
“…The MECIII cells and Island cells appear less important for spatial contextual memory. Instead, the hippocampal CA3 region may be crucial for the formation of spatial contextual memory (Nakazawa et al 2003;Nakashiba et al 2008). Thus, the trisynaptic pathway from Ocean cells in ECII to CA1 via the trisynaptic circuit may primarily process spatial context, whereas the direct pathways from MECIII and Island-SL-INs may be responsible for temporal properties of episodic memory.…”
Section: Discussionmentioning
confidence: 99%